Entrapped temporal horn syndrome: a retrospective analysis of 5 case series. Issue 3 (4th May 2022) - Zhuang, Yan; Richard, Seidu A.; Zhou, Jiahao; Liu, Jun; Fang, Zhen; Chen, Zejun
Abstract : Introduction: Entrapped temporal horn (ETH) syndrome is a rare form of localized noncommunicating hydrocephalus, which is often associated with the treatment of lesions around the trigone area (atrium) of the lateral ventricles. So far, only a few cases have been reported in the literature. Thus, we present our experience with the causes and management of patients with ETH syndrome at our institution. Materials and method: We retrospectively analyzed clinical data of 5 patients with ETH syndrome treated at our facility from July 2018 to August 2021. Patients' data such as age, sex, initial disease, clinical presentation, radiologic diagnosis, treatment, and outcomes were documented and analyzed. Results: Our patients comprise of 3 females and 2 males. Their ages ranged from 42 to 85 years, with a mean age of 62 years. Postoperative adhesions caused ETH in 3 patients while meningioma and intracranial infection cause the ETH in 2 patients, respectively. One patient was treated via craniotomy, 3 patients were treated via shunting while 1 patient was treated conservatively. The ETH resolved in 4 patients, while no resolution was attained in 1 patient. Conclusion: Definitive treatments via craniotomy or shunting were capable of resolving the ETHs, while conservative treatment did not result in spontaneous resolution. Unresected meningioma around the trigone of the lateral ventricle is capable of causing the ETH, contrary to the notion that, infection or postoperative adhesions are the key causes of ETH. Thus, neurosurgeons ought to be on a lookout for ETH when treating lesions around the trigone area of the lateral ventricles.